Variables utilizadas por investigadores en Tributaria: revisión documental 2016-2020 (2020)
The accounting profession is one of the most regulated, especially in the tax area where professional activities are normally governed based on regulations. This has created a blurred vision of what can be investigated in that area. The objective of this work is to analyze the variables used by researchers in the tax area who publish their work in specialized journals in the SCOPUS database (2016-2020). For this, a documentary review work of the SCOPUS database is carried out, which compiles more than 95% of the total impact scientific publications specialized in accounting. The main results allow us to define fiscal redirection and innovation as the explanatory variables, contingency, socioeconomic well-being and trade as moderating variables and economic events as the main mediating variable. These results allow a reflection on the trends in tax research and have repercussions on aspects such as the reorientation in the construction of research problems around the tax issue, even a wide range of possibilities that were not considered before. As most of the publications come from North America and Europe, concerns arise about the realities of tax research in Latin America.